Quality of mango fruit from the experimental station of Itaguaí Rio de Janeiro state - Vasconcellos, Hélio de Oliveira; Gava, João Paulo (Pesquisa Agropecuaria Brasileira, 2014)
Fourteen mango (Mangífera indica L.) cultivars from the collection of the Experimental Station of Itaguaí, in Rio de Janeiro State were evaluated for fruit quality. All cultivars showed a pulp yield above 50%. 'São Quirino', 'Manteiga'. 'Carlota' and 'Santa Alexandrina' cultivars presented a pulp yield of 64,8%, 64,0%, 63,6%. 63,2%, respectively. 'Carlota', 'Gôa Alfonso', and 'São Quirino', presented the largest total soluble solids and acidity ratio with, 1:140,7; 1:126,8, and 1:103,0, respectively. The 'Marina' cultivar presented the highest value for fruit acidity, with 0,429%.